Effect of different nutrient management practices on nutrient availability and uptake in Vaikom kari soils of Kuttanad, Kerala - VS, Devi (ORYZA-An International Journal of Rice, 2023)
A field experiment was laid out in RBD with 16 treatments in three replications with rice variety Uma. The treatments were dolomite, lime + MgSO4 or Rice Husk Ash (RHA) + MgSO4 along with 100% package of practice recommendations of Kerala Agricultural University (POP) alone or with 100% POP + foliar spray of 13:0:45 (1%) or borax (0.5%) or 13:0:45 + borax at PI stage. Lime + MgSO4 + 75% POP + 13:0:45 + borax as well as lime without MgSO4 + 100% POP combined with 13:0:45 or borax or both were also included as treatments. The treatment dolomite + POP + 13:0:45 produced the highest grain yield of 5.42 and 5.57 t ha-1 during 2015 and 2016 respectively. This treatment was followed by dolomite + POP + 13:0:45 + borax and lime + POP + MgSO4 + 13:0:45 during both the years. Lower yields were produced by the treatments involving RHA and 75% POP. The pooled analysis of two years’ data also proved the significance of the treatments involving dolomite + POP or lime + POP + MgSO4 on grain yield. The highest yield of 5.49 t ha-1 was recorded by dolomite + POP + 13:0:45 followed by dolomite + POP + 13:0:45 + borax and lime + MgSO4 + POP + 13:0:45. The treatments involving RHA and 75% POP registered significantly lower grain yield in the pooled data. The treatments involving dolomite registered lower status of soil available Fe and higher status of available Mn and B. Higher status of available Zn was registered by the treatments involving dolomite or lime + MgSO4. The treatments involving dolomite, lime + MgSO4 or RHA + MgSO4 along with POP registered higher available Cu in the soil. Dolomite treatments recorded lower status of Na and exchangeable Al in the soil. Dolomite or lime + MgSO4 along with POP + 13:0:45 with or without borax registered higher uptake of Fe, Mn and Zn while dolomite + POP + 13:0:45 with or without borax recorded higher uptake of Cu and B. The treatments involving RHA and 75% POP recorded lower uptake of micronutrients during both the years. Uptake of Na was the highest with RHA + POP + MgSO4 + 13:0:45 during first year and with dolomite + POP during second year. Higher Al uptake was observed with lime + POP + 13:0:45 with or without MgSO4. The grain yield was significantly and positively correlated with the uptake of Mn, Zn, Cu and B and significantly and negatively correlated with Fe during the first year. During the second year, the yield was significantly and positively correlated with uptake of nutrients except Na and Al. The results indicated that amelioration of soil acidity is a crucial management practice for improving the availability and uptake of nutrients resulting in higher yield.